Urgensi Perlindungan Konsumen Di Era Digital (Regulasi, Potensi Dan Tantangan) - elyani elyani (Smart GOALS Jurnal Bisnis Digital Dan Manajemen, 2025)
This study aims to analyze the history of consumer protection in Indonesia, the role of media and information in the digital economy era, and the urgency of legal consumer protection in the digital age concerning regulations, potentials, and challenges. The research employs normative legal methods supported by empirical legal studies using historical, statutory, and conceptual approaches. Primary, secondary, and tertiary data were utilized to support the analysis. The findings reveal that existing regulations, including Law No. 8 of 1999 on Consumer Protection, need revision to address the challenges and risks arising from digital transformation. In conclusion, there is a need for regulatory reforms that are more adaptive to technological advancements to safeguard consumers and support Indonesia's digital economy.